2023
DOI: 10.7717/peerj.15262
|View full text |Cite
|
Sign up to set email alerts
|

Mineral nutrient variability of potato (Solanum tuberosum L.) tubers with different colors grown in Niksar, Kazova and Artova locations of Tokat Province, Turkey

Abstract: Potato is one of the most commonly consumed non-grain staple food crops in the world therefore, the mineral nutrient content of the potato is extremely important for human nutrition. The lack of mineral nutrients causes significant health problems, thus, many of these nutrients are often taken as supplements. This study was carried out to investigate the effects of potato flesh color and location on different mineral nutrient contents under Niksar, Kazova and Artova locations in Tokat Province, Turkey, during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Potato (Solanum tuberosum L.) one of the most important plants, serving as a major dietary staple in many countries due to its mineral content (Singh et al, 2021, Karan 2023. Potato tubers are an important item in the diet of the average Pole, due to their high bioavailability of minerals (Burligame et al, 2009, White et al, 2009, Alamar et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Potato (Solanum tuberosum L.) one of the most important plants, serving as a major dietary staple in many countries due to its mineral content (Singh et al, 2021, Karan 2023. Potato tubers are an important item in the diet of the average Pole, due to their high bioavailability of minerals (Burligame et al, 2009, White et al, 2009, Alamar et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…HarvestPlus, one component of the Consortium of International Agricultural Research Centers (CGIAR) research program on agriculture for nutrition and health, and its collaborators have demonstrated the effectiveness of plant breeding in alleviating micronutrient deficiencies since 2003 (Bouis and Saltzman, 2017). In potatoes, the mineral content of tubers is influenced by genetic and environmental factors (Karan, 2023), making breeding more challenging. For the past couple of decades, the International Potato Center (CIP) has been working on potato mineral biofortification to raise the amount of iron and zinc (Burgos et al, 2020), but other potato breeding programs have placed more emphasis over the past few decades on increasing yield potential, processing quality, and improving disease/pest resistances, typically without paying much attention to the mineral composition of tubers.…”
Section: Introductionmentioning
confidence: 99%